New insights into Late Devonian vertebrates and associated fauna from the Cuche Formation (Floresta Massif, Colombia) (2019)
New vertebrate remains are reported from the Late Devonian (?Frasnian) Cuche Formation of northeastern Colombia, including a new taxon of antiarch placoderm (Colombialepis villarroeli, gen. et sp. nov., previously reported as Asterolepis) and a new taxon of arthrodiran placoderm (Colombiaspis rinconensis, gen. et sp. nov.). We also report evidence of a stegotrachelid actinopterygian, a diplacanthid acanthodian (cf. Florestacanthus morenoi), a second antiarch placoderm (Bothriolepis sp.), a putative megalichthyid, and a putative tristichopterid. The absence of typical Euramerican markers, e.g., Asterolepis and Strepsodus, in this assemblage suggests that faunal interchange between Euramerica and Gondwana was less pronounced during the Frasnian-Famennian than previously thought (i.e., the Great Devonian Interchange hypothesis). Three arthropod taxa, including two families of spinicaudatan branchiopods and the eurypterid Pterygotus cf. bolivianus, are found to be associated with the reported vertebrate fauna. Pterygotus cf. bolivianus represents the first eurypterid described from Colombia and the youngest known pterygotid eurypterid, highlighting that pterygotids, which were competitors for large predatory fishes, did not go extinct during the major vertebrate radiation in the Early and Middle Devonian.